The Multiple Determinants of Maternal Parenting Stress 12 Months After Birth: The Contribution of Antenatal Attachment Style, Adverse Childhood Experiences, and Infant Temperament - Moe, Vibeke; von Soest, Tilmann; Fredriksen, Eivor; Olafsen, Kåre S.; Smith, Lars (Frontiers in Psychology, 2018)
Parenting stress can influence caregiving behavior negatively, which in turn may harm children’s development. Identifying precursors of parenting stress, preferably beginning during pregnancy and throughout the first year of life, is therefore important. The present study aims to provide novel knowledge on this issue through a detailed examination of the association between maternal attachment style and later parenting stress. Moreover, we examine the role of several additional risk factors, specificially the mothers’ own adverse childhood experiences (ACE), as well as infants’ temperamental characteristics. Data from a community based longitudinal study of 1,036 Norwegian mothers, collected during pregnancy and 12 months after childbirth, were used. Results showed that attachment style in pregnancy predicted parenting stress 1 year after birth. In addition, it was demonstrated that the mothers’ own ACEs predicted postnatal parenting stress, and that attachment style operated as a mediator of this association. A significant association between perceived infant temperament and parenting stress was also found. The study illustrates the importance of understanding the multifactorial antecedents of parenting stress. The results may inform early intervention efforts aimed at supporting mothers and their partners in the potentially difficult transition period around childbirth.